2008
DOI: 10.2174/1874372200802010018
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines Levels in Children Affected by Atopic and Nonatopic Eczema

Abstract: Abstract:Patients with atopic eczema present higher serum levels of total IgE and different pattern of cytokines, compared to nonatopic eczematous patients. This study aimed to evaluate serum levels of IL-2, IL-4, IL-5, IL-10, IFN , TNF in eczematous children in relation to atopic and nonatopic form. We enrolled 45 eczematous children and 12 controls. Total IgE and specific IgE against principal food and inhalant allergens were evaluated by UniCap1000 and levels of cytokines by Cytometric Bead Array System. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…With regards to Th1 cytokines, there was two to three times higher mean value of IL-12 and IL-18 , four times higher mean value of serum IFN-γ, one and half times higher mean value of TNF-α in chronic AD patients than acute one . In accordance to the present results, Ricci and colleagues [14], found that patients affected by eczema showed serum levels of IL-4, IL-5, IL-2, IL-10 higher than controls, confirming that, Th2 cells play an important role in the pathogenesis of this form. Katsunuma et al [15] assessed the transcription and production of IFN-γ and IL-5 in peripheral blood mononuclear cells of patients affected by severe eczema.…”
Section: Discussionsupporting
confidence: 93%
“…With regards to Th1 cytokines, there was two to three times higher mean value of IL-12 and IL-18 , four times higher mean value of serum IFN-γ, one and half times higher mean value of TNF-α in chronic AD patients than acute one . In accordance to the present results, Ricci and colleagues [14], found that patients affected by eczema showed serum levels of IL-4, IL-5, IL-2, IL-10 higher than controls, confirming that, Th2 cells play an important role in the pathogenesis of this form. Katsunuma et al [15] assessed the transcription and production of IFN-γ and IL-5 in peripheral blood mononuclear cells of patients affected by severe eczema.…”
Section: Discussionsupporting
confidence: 93%
“…An effect of IL‐4 and IL‐13 on local CYP activities in inflamed skin cannot be ruled out, in that the orally administered probe substrates used in this study are likely primarily eliminated by hepatic metabolism. In general, Type 2 inflammation during atopic disease does not directly involve the liver, and the reported concentrations of circulating IL‐4 and IL‐13 in atopic diseases are only modestly elevated, even during more severe inflammation, with considerable overlap in these cytokine concentrations between AD patients and the general population . Elevation of C‐reactive protein (CRP), an acute phase protein produced in the liver and primarily regulated by IL‐6, has been reported in some patients with AD .…”
Section: Discussionmentioning
confidence: 99%
“…In general, Type 2 inflammation during atopic disease does not directly involve the liver, and the reported concentrations of circulating IL-4 and IL-13 in atopic diseases are only modestly elevated, even during more severe inflammation, with considerable overlap in these cytokine concentrations between AD patients and the general population. [25][26][27][28][29][30][31] Elevation of C-reactive protein (CRP), an acute phase protein produced in the liver and primarily regulated by IL-6, 44 has been reported in some patients with AD. 45 This suggests some degree of influence of Type 2 inflammation on liver metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations